Surgical significance of variations in anatomy in the biliary region - Hassan, Ashfaq Ul; Zargar, Showqat A.; Malik, Aijaz; Shah, Pervez (International Journal of Research in Medical Sciences, 2017)
Variations in the anatomy of the gallbladder, the bile ducts, and the arteries that supply them and the liver are important to the surgeon, because failure to recognize them can cause iatrogenic injury to the biliary tract. A surgeon should be always be careful while operating in this area. In addition these anomalies are associated with a range of other congenital anomalies, including biliary atresia and cardiovascular or other gastrointestinal malformations, biliary lithiasis, choledochal cyst, anomalous pancreaticobiliary junction etc, so a look out for other anomalies should be carried out simultaneously.